Primary MRSA Myositis Mimicking Septic Arthritis - Mohammad Abu-Abaa; Amy Pulikeyil; Hassaan Arshad; Daniel Goldsmith (Case Reports in Critical Care)
As the incidence of bacterial myositis and pyomyositis in the United States is rising, we aim to highlight the presentation of bacterial myositis which is known as a great imitator in tropical regions. This is a case report of a 61-year-old female patient with poorly controlled diabetes who presented initially with lateral hip pain and tenderness. This was initially believed to be septic arthritis and warranted arthrocentesis. What makes this case interesting is that what was believed to be a primary community-acquired MRSA myositis, which progressed to a life-threatening septic shock, happened in a nontropical area (Northeastern USA) and in a patient with no underlying recent muscle injury. This case serves to remind clinicians that infectious myositis is gaining more incidence in nontropical regions and can masquerade as septic arthritis, requiring a high index of suspicion. Normal muscle enzymes like CK and aldolase do not rule out myositis.